2022
DOI: 10.3390/biomedicines10102557
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Antioxidants in Remyelination and Skeletal Muscle Recovery

Abstract: Inflammatory, oxidative, and autoimmune responses cause severe damage to the nervous system inducing loss of myelin layers or demyelination. Even though demyelination is not considered a direct cause of skeletal muscle disease there is extensive damage in skeletal muscles following demyelination and impaired innervation. In vitro and in vivo evidence using exogenous antioxidants in models of demyelination is showing improvements in myelin formation alongside skeletal muscle recovery. For instance, exogenous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 113 publications
0
1
0
Order By: Relevance
“…The role of ketone bodies, especially βHB, in the central nervous system is also important, as it has been shown that they restore neuronal myelin and reduce levels of reactive oxygen species (ROS) and inflammation [71]. Therefore, inflammation is reduced through both pathways (EGCG and increased ketone bodies), which is associated with improved myelin and recently linked to an increase in muscle mass [72].…”
Section: Discussionmentioning
confidence: 99%
“…The role of ketone bodies, especially βHB, in the central nervous system is also important, as it has been shown that they restore neuronal myelin and reduce levels of reactive oxygen species (ROS) and inflammation [71]. Therefore, inflammation is reduced through both pathways (EGCG and increased ketone bodies), which is associated with improved myelin and recently linked to an increase in muscle mass [72].…”
Section: Discussionmentioning
confidence: 99%
“…In collected muscle samples, myosin heavy chain isoform distribution will be assessed by Sodium Dodecyl Sulphate -PolyAcrylamide Gel Electrophoresis (SDS-PAGE), while levels of markers as PGC1alpha will be investigated by ELISA or western blot. Proteomics analysis will be conducted by Liquid Chromatography Mass Spectrometry (LC-MS), using TMT quantification, whereas lipidomics and sphingolipidomics analyses will be conducted by untargeted and targeted LC-MS. [37][38][39][40][41][42] Both the serum proteome and the biochemical characteristics of muscle present differences between men and women. Therefore, only men will be recruited so that varied proteins cannot be attributable to gender differences but to the intervention of patient.…”
Section: Biological Sampling and Analysesmentioning
confidence: 99%
“…The development of inflammatory and tissue regeneration disorders is largely due to an imbalance between reactive oxygen species (ROS) and endogenous antioxidants. Perez and colleagues (2022) reviewed the relationship between the effects of antioxidants on neuronal remyelination and muscle regeneration [23]. In summary, it was pointed out that if the remyelination of damaged nerve cells is inadequate, the regeneration of muscle cells will not be efficient.…”
mentioning
confidence: 99%